MASA KEMUNDURAN (1250-1500 M) - Siregar, Anggita Pratiwi; Khaira, Annisau; Khairatunnisa, Khairatunnisa; Hutasuhut, Raudatan Hasanah; Yasir, Muhammad (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
The history of Islamic civilization, particularly the period of decline (1250–1500 AD), remains a significant field of study attracting scholars from both Muslim and non-Muslim backgrounds. Studying the history of Islamic civilization and culture allows for a deeper understanding of Islam’s golden eras, which fosters a sense of pride and confidence within the Muslim community. This research employs a qualitative approach through a comprehensive literature study. This methodology enables the author to systematically analyze and address research problems by drawing from highly credible sources, including authoritative books and reputable journal articles. The findings suggest that the 1250–1500 AD period was an era of profound challenges for the Islamic world, characterized by a series of events that impacted political, economic, and intellectual landscapes. Despite this decline, Islamic civilization successfully preserved the continuity of its scientific and cultural heritage, providing a crucial foundation for future developments even under adverse conditions